Meiotic Chromosome Stability and Suppression of Crossover Between Non-homologous Chromosomes in xBrassicoraphanus, an Intergeneric Allotetraploid Derived From a Cross Between Brassica rapa and Raphanus sativus - Park, Hye Rang; Park, Jeong Eun; Kim, Jung Hyo; Shin, Hosub; Yu, Seung Hwa; Son, Sehyeok; Yi, Gibum; Lee, Soo-Seong; Kim, Hyun Hee; Huh, Jin Hoe (Frontiers in Plant Science, 2020)
Hybridization and polyploidization are major driving forces in plant evolution. Allopolyploids can be occasionally formed from a cross between distantly related species but often suffer from chromosome instability and infertility. xBrassicoraphanus is an intergeneric allotetraploid (AARR; 2n=38) derived from a cross between Brassica rapa (AA; 2n=20) and Raphanus sativus (RR; 2n=18). xBrassicoraphanus is fertile and genetically stable, while retaining complete sets of both B. rapa and R. sativus chromosomes. Precise control of meiotic recombination is essential for the production of balanced gametes, and crossovers (COs) must occur exclusively between homologous chromosomes. Many interspecific hybrids have problems with meiotic division at early generations, in which interactions between non-homologous chromosomes often bring about aneuploidy and unbalanced gamete formation. We analyzed meiotic chromosome behaviors in pollen mother cells (PMCs) of allotetraploid and allodiploid F1 individuals of newly synthesized xBrassicoraphanus. Allotetraploid (AARR) xBrassicoraphanus PMCs showed a normal diploid-like meiotic behavior. By contrast, allodiploid (AR) xBrassicoraphanus PMCs displayed abnormal segregation of chromosomes mainly due to the absence of homologous pairs. Notably, during early stages of meiosis I many of allodiploid xBrassicoraphanus chromosomes behave independently with few interactions between B. rapa and R. sativus chromosomes, forming many univalent chromosomes before segregation. Chromosomes were randomly assorted at later stages of meiosis, and tetrads with unequal numbers of chromosomes were formed at completion of meiosis in allodiploid xBrassicoraphanus. Immunolocalization of HEI10 protein mediating meiotic recombination revealed that COs normally occurred in allotetraploid xBrassicoraphanus, whereas a smaller number of recombination foci were formed in allodiploid xBrassicoraphanus. These findings suggest that structural dissimilarity between B. rapa and R. sativus chromosomes prevents non-homologous interactions between the parental chromosomes in xBrassicoraphanus, allowing normal diploid-like meiosis. This study also suggests that CO suppression between non-homologous chromosomes is required for correct meiotic progression in newly synthesized allopolyploids, which is important for the formation of viable gametes and reproductive success in the hybrid progeny.